Quality of Life in Children with Type 1 Diabetic – A Systematic Review - Merlin Suji1 , Anita Y. Nawale2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background :Quality of life (QOL) is commonly used in the health care industry to assess the general wellbeing of the individual. Assessing QOL among children with diabetes, is completed with a disease specificapproach.1 The main aim of the present study was to systematically review the characteristics of publishedstudies in children with type 1 diabetic Quality of life and examine the quality of their findings.Method and Material: The 141 research articles searched in (PubMed, Web of Science, CINAHL, Scopus,Academia ,open access ) databases using the following search terms: “type 1 diabetic” and “quality of life”. Depending on the inclusion and exclusion criteria studies were filtered and 12 studies were chosen forthe final analysis. This systematic review was designed and conducted with the Published Guidelines forReporting Systematic Reviews and Meta-Analyses (PRISMA)Result : The studies showed that sampling size differs in each study from 20 till 3005 it selected . butin many studies sample size is below 100. Validity and reliability were not done in many studies. Forreliability al studies who mentioned about validity used Cronbach’s ? coefficient to check the tool efficiency.Studies showed that people with diabetes had lower QoL . however the Quality of Life is directly relatedto the disease condition, HbA1 c and glycaemic control of children . Better control of Diabetic Mellitus isassociated with better health related QoL.